Extracellular Vesicles as Protagonists of Diabetic Cardiovascular Pathology - Gustafson, Dakota; Veitch, Shawn; Fish, Jason E. (Frontiers in Cardiovascular Medicine, 2017)
Extracellular vesicles represent an emerging mechanism of cell-cell communication in the cardiovascular system. Recent data suggest that extracellular vesicles are produced and taken up by multiple cardiovascular cell types, influencing target cells through signaling or transfer of cargo (including proteins, lipids, mRNA, and non-coding RNA). The concentration and contents of circulating extracellular vesicles are altered in several diseases, and represent explicit signatures of cellular activation, making them of particular interest as circulating biomarkers. Extracellular vesicles also actively contribute to the progression of various cardiovascular diseases, including diabetes-related vascular disease. Understanding the relationships between circulating extracellular vesicles, diabetes, and cardiovascular disease is of importance as diabetic patients are at elevated risk for developing several debilitating cardiovascular pathologies, including diabetic cardiomyopathy, a disease that remains an enigma at the molecular level. Enhancing and exploiting our understanding of extracellular vesicle biology could facilitate the development of effective non-invasive diagnostics, prognostics, and therapeutics. This review will focus on extracellular vesicle biology in diabetic cardiovascular diseases, including atherosclerosis and diabetic cardiomyopathy. We will review extracellular vesicle biogenesis and functional properties, as well as provide insight into their emerging role in cell-cell communication. Finally, we will address the utility of extracellular vesicles as clinical biomarkers and outline their impact as a biomedical tool in the development of therapeutics.